2023
DOI: 10.1021/acsapm.3c00169
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Thermoelectric Design Inspired by Ionic Liquid Microemulsion-Based Gel with Regulatable Dual-Temperature Responsiveness

Abstract: The concept and principles of chromatic engineering of electrolytes have demonstrated charming prospects for constructing pluralistic electrochromic devices. Here, we develop a synthetic design bearing thermochromic and electrochromic behaviors based on the ionic liquid (IL) microemulsion-based gel, driven by the intrinsic thermodynamic stability of microemulsion and ionic conductivity of IL. The prepared gel can tune light-scattering behaviors as the droplet expanded or aggregated when the temperature is out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…A thermochromic ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM]TFSI) microemulsion-based gel is prepared by polymerizing an acrylamide monomer in an ionic liquid-based microemulsion. 149 Tween 20 is distributed at the oil–water interface to stabilize the droplets in the ionic liquid microemulsion. At 25 °C, the droplets are stable and difficult to precipitate.…”
Section: Thermochromic Smart Windows For Solar Modulationmentioning
confidence: 99%
“…A thermochromic ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIM]TFSI) microemulsion-based gel is prepared by polymerizing an acrylamide monomer in an ionic liquid-based microemulsion. 149 Tween 20 is distributed at the oil–water interface to stabilize the droplets in the ionic liquid microemulsion. At 25 °C, the droplets are stable and difficult to precipitate.…”
Section: Thermochromic Smart Windows For Solar Modulationmentioning
confidence: 99%
“…Heating, ventilation, and air-conditioning (HVAC) systems account for approximately 40–60% of the energy usage in buildings or 15% of the world’s total energy consumption. Statistical surveys show that increasing the cooling temperature by 1 °C can reduce the building energy consumption by 10–25%. , Generally, glass windows are considered the least energy-efficient part of the building envelope structure. 82% transmittance means that most of the sunlight can enter the room through the glass window, increasing the cooling load. , About one-third of the building energy consumption is wasted on windows due to the high thermal conductivity of inorganic glass reaching 1.1 W m –1 K –1 . , To address this issue, improving the window energy efficiency is crucial for energy conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Heating, ventilation, and air-conditioning (HVAC) systems account for approximately 40–60% of the energy usage in buildings or 15% of the world’s total energy consumption. 1 3 Statistical surveys show that increasing the cooling temperature by 1 °C can reduce the building energy consumption by 10–25%. 4 , 5 Generally, glass windows are considered the least energy-efficient part of the building envelope structure.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive hydrogels have recently received notable attention due to their numerous advantages, such as their excellent stretchability, high flexibility, soft-and-wet nature, , mechanical deformation, and environmental stimuli that can be converted into electrical signals. These superior characteristics have allowed them to be ideal candidates for diverse applications such as human–machine interfaces, soft robots, electrochromic devices, supercapacitors, , implantable biosensors, electrostimulated drug release units, plant culture substrate, human health monitoring, tissue repair materials, , and artificial skin . The preparation methods, however, have always been burdened by laborious and time-consuming manufacturing processes, as well as the additional input of external energy, to satisfy all of these stringent requirements. For example, the preparation strategy for polyacrylic acid (PAA)-based conductive hydrogels usually requires lots of time and energy for the cleavage of initiators such as ammonium persulfate (APS) to initiate the polymerization reaction. Especially, the prepared hydrogels displayed a huge deformation and even damage when exposed to external forces, which greatly reduced their sensitivity and service life. , To address this issue, the development of self-healing hydrogels has been extensively studied by introducing dynamic covalent bonding into the hydrogel network. , Due to their dynamic qualities and simplicity of synthesis, boronate ester linkages generated by the interaction of boronic acid with cis -diols have been frequently employed to prepare multifunctional hydrogels. , Lin et al, for example, reported a multiple sensing hydrogel via boronic ester bonds based on Ag/TA/CNC nanohybrids, PVA, and borax.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive hydrogels have recently received notable attention due to their numerous advantages, such as their excellent stretchability, 1 high flexibility, soft-and-wet nature, 2,3 mechanical deformation, and environmental stimuli that can be converted into electrical signals. 4−7 These superior characteristics have allowed them to be ideal candidates for diverse applications such as human−machine interfaces, 8 soft robots, 9 electrochromic devices, 10 supercapacitors, 11,12 implantable biosensors, 13 electrostimulated drug release units, 14 plant culture substrate, 15 human health monitoring, 16−18 tissue repair materials, 19,20 and artificial skin. 21 The preparation methods, however, have always been burdened by laborious and time-consuming manufacturing processes, 22 as well as the additional input of external energy, to satisfy all of these stringent requirements.…”
Section: ■ Introductionmentioning
confidence: 99%